Anästhesie: Partner oder Konkurrent? = Anesthesiology : partner or competitor? - Körner, Christian; Weigand, Markus A.; Martin, Evgenia (Der Chirurg, 2012)
Surgery and anesthesiology have always been closely connected. Within the increasing complexity of therapies and technical capabilities both subjects overlap in certain areas. This article deals with the question whether anesthesiology is acting as a partner or competitor in the cooperation with the various operative specialties. In several studies it has been shown that the outcome of surgical patients can be improved by communication and interaction with anesthesiology and that forming multidisciplinary teams will be highly beneficial for patients in intensive care units.